Listed government linked companies (GLCs) in Malaysia: an evaluation through financial ratios, cash flow and macroeconomic factors - Jamaltul Nizam, Shamsuddin (2019)
This research is to identify the performance of listed Government Linked-Companies (GLCs) using the financial ratios, cash flow from operating and macroeconomic factors. II years of performance was studied from 2007 to 2017. Data were extracted from the annual reports of company and included information from the income statement, balance sheet, cash flow statement and notes to the accounts published in Bursa Malaysia websites. The study covered 44 Government Linked Companies consist of 11 non-Shariah and 33 Shariah compliant that listed in Kuala Lumpur Stock Exchange. STATA 15 software was used in order to analyze the data by using diagnostic test, panel data test and hierarchal panel regression test. Panel regression tests have been used to determine the relationship of the variables. The findings of the study show there is a significant impact in the results through the different performance result of Government Linked Companies when using financial ratios and cash flow from operating and macroeconomic factors. The study also found that cash flow from operating influence the profitability for all GLCs and non-Shariah of listed Government Linked-Companies in Malaysia with other internal and external variables. Besides, providing suggestions for further research work, this study provides several recommendations for researcher to obtain more comprehensive analysis of the profitability of GLCs.